Trends in suicide attempts and suicide mortality in Belize 2019-2023 - Oladeji, Olusola; Nah, Edgar; Kirsch, Jaclyn; Manzanero, Russell; Legins, Ken; Oladeji, Anjola; Simons, Juliet; Baitwabusa, Angella Edith; Quintanilla, Iveth (International Journal Of Community Medicine And Public Health, 2025)
Background: Suicide and attempts present significant public health challenges, especially with the increasing prevalence of suicides carried out using violent means. This study aimed to analyze trends in suicide mortality and attempts, methods used, and gender differences in Belize from 2019 to 2023. Methods: This retrospective quantitative study utilized secondary data from the Belize Health Information System for the period 2019 to 2023. Results: The rate of attempted suicides decreased from 28.43 per 100,000 population in 2019 to 2022, then increased to 26.16 per 100,000 population in 2023. Conversely, the suicide rate steadily rose from 6.99 per 100,000 population in 2019 to 11.38 per 100,000 population in 2023. Attempted suicides were most prevalent among adolescents aged 15-19 years, while suicides were highest among individuals aged 15-34years. Females had a higher rate of attempted suicides, whereas males had a higher suicide mortality rate. The male-to-female suicide ratio varied from 2.38 in 2019 to 7.75 in 2021 and 3.60 in 2023. Poisoning via medication overdose was the most common method for attempted suicides, while hanging was the most common method for suicides, with no significant gender differences in methods used. Mental health and substance-induced disorders were the most frequently reported risk factors for both suicide and attempted suicide. Conclusions: This study provides a comprehensive analysis of suicide attempts and mortality trends in Belize, highlighting the alarming increase in suicide rates as a serious public health concern. These findings underscore the urgent need for a multi-sectoral approach to suicide prevention.